2010
DOI: 10.2478/s11535-009-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of metal concentrations in periphyton and taxonomic composition of the algal community at a Yenisei River littoral site

Abstract: The concentrations of metals K, Na, Ca, Mg, Fe, Mn, Zn, Cu, Ni, Pb, Co and Cr, in the water and periphyton (epilithic algal communities) were studied at a site in the middle stream of the Yenisei River (Siberia, Russia) during three years using monthly sampling frequencies. Despite considerable seasonal variations in aquatic concentrations of some metals, there was no correlation between metal contents in the water and in periphyton. Seasonal concentration variations of some metals in periphyton were related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…We concluded that increasing nutrient concentrations travelling downstream were the main factors causing the changes in the periphyton communities, and this agrees with the results of a study conducted by Kelly [29]. As has been shown previously, seasonal variations in the concentrations of some metals in river periphyton can be related to variations in the periphytic algae and cyanobacteria species present [30]. Therefore, we believe that the changes in the periphytic assemblages we found may have been connected with heavy metal accumulation by the periphyton.…”
Section: Resultssupporting
confidence: 91%
“…We concluded that increasing nutrient concentrations travelling downstream were the main factors causing the changes in the periphyton communities, and this agrees with the results of a study conducted by Kelly [29]. As has been shown previously, seasonal variations in the concentrations of some metals in river periphyton can be related to variations in the periphytic algae and cyanobacteria species present [30]. Therefore, we believe that the changes in the periphytic assemblages we found may have been connected with heavy metal accumulation by the periphyton.…”
Section: Resultssupporting
confidence: 91%
“…Detailed hydroecological descriptions of the study site are given elsewhere (Sushchik et al, 2006;Kolmakov et al, 2008;Anishchenko et al, 2010;Kalachova et al, 2011;Gladyshev et al, 2012a,b). Briefly, dominant species in the epilithon in spring and early summer are green algae in the genus Ulothrix.…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…In summer, the biofilm is mostly composed of diatoms, where several dominant species of the genera Gomphonema, Didymosphaenia, Fragilaria, Aulacoseira and Cymbella replace each other. In the late autumn and winter, cyanobacteria of genera Chamaesiphon, Oscillatoria and Phormidium become dominant (Kolmakov et al, 2008;Anishchenko et al, 2010;Sushchik et al, 2010).…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…The epilithic microalgae at the site are described in details elsewhere [20,21]; to summarize, the microalgal biomass was very high in spring and early summer, reaching ca. 1 000 g m −2 wet weight, at the expense of green algae.…”
Section: Study Sitementioning
confidence: 99%